2021
DOI: 10.5937/jomb0-27945
|View full text |Cite
|
Sign up to set email alerts
|

Stability of hematological analytes during 48 hours storage at three temperatures using Cell-Dyn hematology analyzer

Abstract: Background: The complete blood count (CBC) with differential leukocyte count (DLC) is one of the most common tests requested by physicians. The results of this test are affected by storage temperature and time of incubation. This study was designed to evaluate the stability of hematologic parameters in blood specimens stored for 48 hours at three temperatures. Methods: K2 EDTA- blood was collected from 22 apparently healthy adults. The CBC was performed using Cell-Dyn 3700 hematology analyzer (Abbott Dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…9,10 In regular haematological workup, more than 70% of all errors commonly occurs during preanalytical phase which includes preparation of patient, collection, transportation, storage of collected blood samples & preparation for analysis. 11 It is also necessary to consider the environmental temperature at different places, particularly in hot climate areas e.g. southern countries which affects stability of hematological parameters & final results.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 In regular haematological workup, more than 70% of all errors commonly occurs during preanalytical phase which includes preparation of patient, collection, transportation, storage of collected blood samples & preparation for analysis. 11 It is also necessary to consider the environmental temperature at different places, particularly in hot climate areas e.g. southern countries which affects stability of hematological parameters & final results.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation showed that EPS foam shaped into a six-faced cuboid with external dimensions (length x width x height) of 24 cm x 14 cm x 18 cm was the best material to be used for drone carriage due to its ability to maintain optimal mean kinetic temperature for blood sample transportation, which was 4.70 ± 1.14°C. Unalli et al (2021) reported that the best storage temperature to maintain hematological analytes in EDTA tubes over 12 hours was 4°C [ 30 ]. This result is in congruence with the current practice in Malaysia where the EPS foam storage box is used to transport blood samples using ground vehicles such as motorcycles or ambulance [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…We would like to thank the Director General of Health Malaysia, Tan Sri Dr Noor Hisham Abdullah for his permission to publish this article (Reference Number: NIH.800-4/4/1. Jld 94 (30)). We thank our colleagues and staff from the Ministry of Health (MOH), Malaysia, who provided insight and expertise that greatly assisted this research.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…RDW is reported by all hematology instruments in clinical use and is expressed as the standard distribution (RDW-SD) or coefficient of variation (RDW-CV) for the red blood cell histogram. Several preanalytical variables may impact RDW and be a source of bias, including storage time, storage temperature, tube type, and transport conditions [2] , [3] , [4] , [5] , [6] , [7] , [8] . In addition, there is a lack of harmonization for RDW reporting by different instrument manufacturers [9] .…”
mentioning
confidence: 99%